A kind of solid-supported platinum catalyst, polyether-modified siloxane and preparation method
By using the impregnation method to prepare solid-loaded combined platinum catalysts in the synthesis of polyether modified siloxanes, the problem of difficulty in recycling and utilization of the catalysts is solved, efficient and economical catalytic effects are achieved, and product quality and wetting performance are improved.
Patent Information
- Application Number
- CN202211640524.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-20
AI Technical Summary
The existing homogeneous platinum catalysts are difficult to recycle and utilize during the synthesis of polyether modified siloxanes, resulting in waste of precious metal platinum and low catalytic activity, affecting product quality.
The solid-supported compound platinum catalyst was prepared by impregnation method, and the loading and activity of the catalyst were improved by combining polyethylene glycol as a complexing agent with the platinum source and support.
The catalyst is reusable, production costs are reduced, the catalytic activity and product quality of polyether modified silicones are improved, and the product appearance is clear and transparent, with excellent wetting properties.
Smart Images

Figure BDA0004008740610000031 
Figure BDA0004008740610000032 
Figure BDA0004008740610000033
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of platinum catalysts, and in particular relates to a solid-supported complex platinum catalyst, a polyether-modified siloxane and a preparation method. Background Art
[0002] Polyether modified siloxane can be divided into hydrolyzable and non-hydrolyzable types according to the connection form between the silicon atom on the siloxane segment and the polyether segment. The hydrolyzable type is connected by Si-OC bond, and its structure is unstable and easy to hydrolyze; while the non-hydrolyzable type is connected by Si-C bond, and its structure is stable and not easy to hydrolyze. Due to the special structural properties of non-hydrolyzable polyether modified siloxane, it has become the largest variety in modified siloxane products, showing broad application prospects in many fields such as textiles, light industry, medical treatment, and coatings.
[0003] At present, the synthesis of polyether-modified siloxane mainly utilizes the hydrosilylation reaction between siloxane and polyether. This type of reaction can only be carried out under the action of a catalyst. At present, on the one hand, the reaction can be catalyzed by ultraviolet light, peroxides, azo compounds or heating, but it is greatly limited due to poor selectivity and the occurrence of side reactions such as the polymerization of unsaturated bonds that are difficult to avoid in some systems. On the other hand, transition metals such as platinum, palladium and germanium can be used as catalysts for the reaction.
[0004] At present, the catalyst for synthesizing polyether-modified siloxane is mainly homogeneous platinum catalyst, which needs to be reacted with organic solvent first and then coexist with reactants in liquid phase for hydrosilylation reaction. However, it is difficult to separate and recycle the used catalyst from the system, resulting in waste of precious metal platinum. At the same time, the catalyst residue in the product is easy to corrode metal containers and affect the color and appearance of the product. In addition, it has the defect of low catalytic activity for certain reactions, resulting in poor quality of the final product.
[0005] In summary, it is particularly important to find a green, economical and easy-to-prepare catalyst and apply it to the hydrosilylation reaction system to prepare polyether-modified siloxanes with excellent performance. Summary of the invention
[0006] In view of the defects of the existing technology, the present invention provides a solid-supported platinum catalyst, a polyether-modified siloxane and a preparation method.
[0007] In order to achieve the above purpose, the embodiment of the present invention provides the following technical solutions:
[0008] According to a first aspect of an embodiment of the present invention, the present invention provides a method for preparing a solid-supported complex platinum catalyst, comprising:
[0009] Dissolving polyethylene glycol and a platinum source in ethanol to obtain a mixed solution;
[0010] Adding a carrier, impregnating, and drying to obtain the immobilized complex platinum catalyst;
[0011] Wherein, the platinum source is chloroplatinic acid-isopropanol solution, and the molar concentration of platinum element in the mixed solution is 0.01-0.04 mol / L.
[0012] The present invention finds that when an immobilized complex platinum catalyst is prepared by an impregnation method, the use of polyethylene glycol can significantly increase the loading amount of the impregnation solution on the carrier, thereby improving the activity of the obtained catalyst.
[0013] Furthermore, the polyethylene glycol is used as a complexing agent, and the mass volume ratio of the polyethylene glycol to ethanol is 1.5-2.5 g:15 mL.
[0014] Furthermore, the carrier is silica gel, Al2O3 or activated carbon, and the mass ratio of the carrier to polyethylene glycol is 4.0-6.0:1.5-2.5.
[0015] Furthermore, the immersion time is 24 to 36 hours, and the drying temperature is 80 to 100°C.
[0016] According to a second aspect of an embodiment of the present invention, the present invention provides an immobilized complex platinum catalyst, which is prepared by the method described in any one of the above items.
[0017] According to a third aspect of an embodiment of the present invention, the present invention provides a method for preparing a polyether-modified siloxane, comprising the following steps:
[0018] The polyether and the immobilized platinum catalyst as described above are heated at 75-80°C for 30-60 minutes, then siloxane is added and the temperature is raised to 120-140°C for 5-8 hours. The siloxane has a molecular weight of 250-20,000 and a hydrogen content of 0.2%-1.0%.
[0019] Furthermore, the molar ratio of the siloxane to the polyether is 1.0:1.0-1.5; based on the total mass of the siloxane and the polyether, the amount of the immobilized platinum catalyst is 10-35 μg / g.
[0020] In some specific embodiments, the preparation method of polyether-modified siloxane is as follows: polyether and the above-synthesized immobilized platinum catalyst are added together into a four-necked flask equipped with a reflux condenser, a thermometer and an agitator, and the two are stirred evenly without the introduction of nitrogen and heated to 75-80°C for catalyst activation for 30-60 minutes, and then the siloxane is added to the above system, and the temperature is raised to 120-140°C for insulation reaction for 5-8 hours. The molar ratio of the added siloxane to the polyether is 1.0:1.0-1.5, the amount of the immobilized platinum catalyst is 10-35 μg / g, and finally the reaction conversion rate of the siloxane in the reaction is determined by the determination of the hydrogen content. After the reaction is completed, the immobilized platinum catalyst is separated by filtration to obtain the polyether-modified siloxane.
[0021] The polyether structural formula is:
[0022]
[0023] Wherein: n=2-7, -R is -H, -CH3 or -CH2CH3.
[0024] The structural formula of siloxane is:
[0025]
[0026] Among them, x, y = 1, 2, 3···, the molecular weight is 250 to 20000, and the hydrogen content is 0.2% to 1.0%.
[0027] The hydrosilylation reaction equation is:
[0028]
[0029] Wherein, x, y = 1, 2, 3, ..., n = integers of 2-7,
[0030] -R is -H, -CH3 or -CH2CH3.
[0031] According to a fourth aspect of the embodiments of the present invention, the present invention provides a polyether-modified siloxane prepared by the method described in any one of the above items.
[0032] The embodiments of the present invention have the following advantages:
[0033] 1. The preparation method of the immobilized platinum catalyst provided by the present invention is simple and easy, can be reused after recovery, and still has high activity after being used four times, which greatly reduces production costs and is environmentally friendly;
[0034] 2. Compared with traditional homogeneous platinum catalysts and common solid-supported catalysts, the solid-supported platinum catalyst proposed in the present invention has the advantages of strong loading and high catalytic activity;
[0035] 3. The preparation method of the polyether-modified siloxane proposed by the present invention is simple, the amount of catalyst used is small, there is no catalyst residue in the product, the product has a clear and bright appearance and has extremely low surface tension and outstanding spreading performance. DETAILED DESCRIPTION
[0036] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Chloroplatinic acid-isopropanol solution: purchased from Nanjing Chemical Reagent Co., Ltd.
[0038] Example 1
[0039] (1) Preparation of immobilized platinum complex catalyst: 2.0 g of polyethylene glycol (PEG) was dissolved in 15 mL of ethanol, and then 4 mL of chloroplatinic acid-isopropanol solution was added. The molar concentration of platinum in the solution was 0.02 mol / L. After stirring evenly, 4.0 g of silica gel was added. After immersion for 24 h, the solution was dried at 80°C to finally prepare an immobilized platinum complex catalyst.
[0040] (2) Preparation of polyether-modified siloxane: 274.37g of allyl polyether and 0.01g of the above-synthesized immobilized platinum catalyst were added to a four-necked flask equipped with a reflux condenser, a thermometer and a stirrer. The two were stirred evenly without the introduction of nitrogen and the temperature was raised to 75-80°C for catalyst activation for 30 minutes. Then 225.63g of siloxane with a molecular weight of 250 and a hydrogen content of 0.5% was added to the above system and the temperature was raised to 120°C for 6 hours of insulation reaction. The molar ratio of the added siloxane to the polyether was 1.0:1.0, and the amount of the catalyst was 20μg / g. Finally, the reaction conversion rate of the silane in the reaction was determined by measuring the hydrogen content. After the reaction was completed, the immobilized platinum catalyst was separated by filtration to obtain polyether-modified siloxane.
[0041] Example 2
[0042] (1) Preparation of immobilized platinum complex catalyst: 2.0 g PEG was dissolved in 15 mL ethanol, and then 4 mL chloroplatinic acid-isopropanol solution was added. The molar concentration of platinum element in the solution was 0.02 mol / L. After stirring evenly, 4.0 g silica gel was added. After immersion for 24 h, the solution was dried at 90° C. to finally prepare an immobilized platinum complex catalyst.
[0043] (2) Preparation of polyether-modified siloxane: 210.92 g of allyl polyether and 0.01 g of immobilized platinum catalyst were added to a flask, stirred evenly without nitrogen, and heated to 75-80°C for catalyst activation for 30 min. Then 289.08 g of siloxane with a molecular weight of 500 and a hydrogen content of 0.5% was added to the above system, and the temperature was raised to 130°C for 6 h. The molar ratio of siloxane to polyether added was 1.0:1.2, and the amount of catalyst was 20 μg / g. Finally, the reaction conversion rate of silane in the reaction was determined by measuring the hydrogen content. After the reaction, the immobilized platinum catalyst was separated by filtration to obtain polyether-modified siloxane.
[0044] Example 3
[0045] (1) Preparation of immobilized platinum complex catalyst: 2.5 g PEG was dissolved in 15 mL ethanol, and then 4 mL chloroplatinic acid-isopropanol solution was added. The molar concentration of platinum in the solution was 0.02 mol / L. After stirring evenly, 4.0 g alumina was added. After immersion for 36 h, the solution was dried at 90 °C to finally prepare an immobilized platinum complex catalyst.
[0046] (2) Preparation of polyether-modified siloxane: 296.68g of allyl polyether and 0.01g of immobilized platinum catalyst were added to a flask, stirred evenly without nitrogen, and heated to 75-80°C for catalyst activation for 30 minutes. Then 203.32g of siloxane with a molecular weight of 250 and a hydrogen content of 0.7% was added to the above system, and the temperature was raised to 130°C for 7 hours. The molar ratio of siloxane to polyether added was 1.0:1.2, and the amount of catalyst was 20μg / g. Finally, the reaction conversion rate of silane in the reaction was determined by measuring the hydrogen content. After the reaction, the immobilized platinum catalyst was separated by filtration to obtain polyether-modified siloxane.
[0047] Example 4
[0048] (1) Preparation of immobilized platinum complex catalyst: 2.5 g PEG was dissolved in 15 mL ethanol, and then 4 mL chloroplatinic acid-isopropanol solution was added. The molar concentration of platinum in the solution was 0.02 mol / L. After stirring evenly, 4.0 g activated carbon was added. After soaking for 36 h, the solution was dried at 80 °C to finally prepare an immobilized platinum complex catalyst.
[0049] (2) Preparation of polyether-modified siloxane: 189.05g of allyl polyether and 0.0075g of immobilized platinum catalyst were added to a flask, stirred evenly without nitrogen, and heated to 75-80°C for catalyst activation for 30 minutes. Then 310.95g of siloxane with a molecular weight of 500 and a hydrogen content of 0.7% was added to the above system, and the temperature was raised to 130°C for 7 hours. The molar ratio of siloxane to polyether added was 1.0:1.0, and the amount of catalyst was 15μg / g. Finally, the reaction conversion rate of silane in the reaction was determined by measuring the hydrogen content. After the reaction, the immobilized platinum catalyst was separated by filtration to obtain polyether-modified siloxane.
[0050] Example 5
[0051] (1) Preparation of immobilized platinum complex catalyst: 2.5 g PEG was dissolved in 15 mL ethanol, and then 4 mL chloroplatinic acid-isopropanol solution was added. The molar concentration of platinum in the solution was 0.02 mol / L. After stirring evenly, 5.0 g alumina was added. After immersion for 36 h, the solution was dried at 90 °C to finally prepare an immobilized platinum complex catalyst.
[0052] (2) Preparation of polyether-modified siloxane: 163.62g of allyl polyether and 0.0075g of immobilized platinum catalyst were added to a flask, stirred evenly without nitrogen, and heated to 75-80°C for catalyst activation for 30 minutes. Then 336.38g of siloxane with a molecular weight of 750 and a hydrogen content of 0.5% was added to the above system, and the temperature was raised to 120°C for 8 hours. The molar ratio of siloxane to polyether added was 1.0:1.2, and the amount of catalyst was 15μg / g. Finally, the reaction conversion rate of silane in the reaction was determined by measuring the hydrogen content. After the reaction, the immobilized platinum catalyst was separated by filtration to obtain polyether-modified siloxane.
[0053] Example 6
[0054] (1) Preparation of immobilized platinum complex catalyst: 2.5 g PEG was dissolved in 15 mL ethanol, and then 4 mL chloroplatinic acid-isopropanol solution was added. The molar concentration of platinum in the solution was 0.02 mol / L. After stirring evenly, 5.0 g activated carbon was added. After immersion for 36 h, the solution was dried at 90 °C to finally prepare an immobilized platinum complex catalyst.
[0055] (2) Preparation of polyether-modified siloxane: 189.05g of allyl polyether and 0.005g of immobilized platinum catalyst were added to a flask, stirred evenly without nitrogen, and heated to 75-80°C for catalyst activation for 30 minutes. Then 310.95g of siloxane with a molecular weight of 500 and a hydrogen content of 0.5% was added to the above system, and the temperature was raised to 120°C for 8 hours. The molar ratio of siloxane to polyether added was 1.0:1.0, and the amount of catalyst was 10μg / g. Finally, the reaction conversion rate of silane in the reaction was determined by measuring the hydrogen content. After the reaction, the immobilized platinum catalyst was separated by filtration to obtain polyether-modified siloxane.
[0056] Example 7
[0057] (1) Preparation of immobilized platinum complex catalyst: 2.5 g PEG was dissolved in 15 mL ethanol, and then 4 mL chloroplatinic acid-isopropanol solution was added. The molar concentration of platinum in the solution was 0.02 mol / L. After stirring evenly, 5.0 g activated carbon was added. After immersion for 36 h, the solution was dried at 90 °C to finally prepare an immobilized platinum complex catalyst.
[0058] (2) Preparation of polyether-modified siloxane: 9.27g of allyl polyether and 0.005g of immobilized platinum catalyst were added to a flask, stirred evenly without nitrogen, and heated to 75-80°C for catalyst activation for 30 minutes. Then 490.73g of siloxane with a molecular weight of 19306 and a hydrogen content of 0.2% was added to the above system, and the temperature was raised to 130°C for 8 hours. The molar ratio of siloxane to polyether added was 1.0:1.2, and the amount of catalyst was 10μg / g. Finally, the reaction conversion rate of silane in the reaction was determined by measuring the hydrogen content. After the reaction, the immobilized platinum catalyst was separated by filtration to obtain polyether-modified siloxane.
[0059] Comparative Example 1
[0060] 274.37g of allyl polyether and 1.22mL of chloroplatinic acid-isopropanol solution were added to the flask, and the two were stirred evenly without nitrogen and heated to 75-80°C for catalyst activation for 30min. Then 225.63g of siloxane with a molecular weight of 250 and a hydrogen content of 0.5% was added to the above system, and the temperature was raised to 120°C for insulation reaction for 6h. The molar ratio of the added siloxane to the polyether was 1.0:1.0, the amount of the catalyst was 20μg / g, the molar concentration of the platinum element in the chloroplatinic acid-isopropanol solution was 0.02mol / L, and the reaction conversion rate of the silane in the reaction was determined by the determination of the hydrogen content. After the reaction, the immobilized platinum catalyst was separated by filtration to obtain a polyether-modified siloxane.
[0061] Comparative Example 2
[0062] 210.92g of allyl polyether and 1.22mL of chloroplatinic acid-isopropanol solution were added to the flask, and the two were stirred evenly without nitrogen and heated to 75-80°C for catalyst activation for 30min. Then 289.08g of siloxane with a molecular weight of 500 and a hydrogen content of 0.5% was added to the above system, and the temperature was raised to 130°C for insulation reaction for 6h. The molar ratio of siloxane to polyether added was 1.0:1.2, the amount of catalyst was 20μg / g, the molar concentration of platinum in chloroplatinic acid-isopropanol solution was 0.02mol / L, and the reaction conversion rate of silane in the reaction was determined by the determination of hydrogen content. After the reaction, the immobilized platinum catalyst was separated by filtration to obtain polyether modified siloxane.
[0063] Comparative Example 3
[0064] 163.62g of allyl polyether and 1.22mL of chloroplatinic acid-isopropanol solution were added to the flask, and the two were stirred evenly without nitrogen gas, and the temperature was raised to 75-80°C for catalyst activation for 30 minutes. Then 336.38g of siloxane with a molecular weight of 750 and a hydrogen content of 0.5% was added to the above system, and the temperature was raised to 120°C for insulation reaction for 8 hours. The molar ratio of the added siloxane to the polyether was 1.0:1.2, the amount of the catalyst was 20μg / g, the molar concentration of the platinum element in the chloroplatinic acid-isopropanol solution was 0.02mol / L, and the reaction conversion rate of the silane in the reaction was determined by the determination of the hydrogen content. After the reaction, the immobilized platinum catalyst was separated by filtration to obtain a polyether-modified siloxane.
[0065] Comparative Example 4
[0066] 9.27g of allyl polyether and 1.22mL of chloroplatinic acid-isopropanol solution were added to a flask, and the two were stirred evenly without nitrogen gas, and the temperature was raised to 75-80°C for catalyst activation for 30 minutes, and then 490.73g of siloxane with a molecular weight of 19306 and a hydrogen content of 0.2% was added to the above system, and the temperature was raised to 130°C for insulation reaction for 8 hours. The molar ratio of the added siloxane to the polyether was 1.0:1.2, the amount of the catalyst was 20μg / g, and the reaction conversion rate of the silane in the reaction was determined by measuring the hydrogen content, and finally the polyether-modified siloxane was obtained.
[0067] The catalyst used in Comparative Examples 1-4 is an isopropanol solution of chloroplatinic acid, and it is difficult to recycle the catalyst after the reaction is completed, which greatly increases production costs and causes a waste of resources. In addition, the reaction product conversion rate is low, and the product color is yellow and the performance is unstable. And with the immobilized platinum catalyst in Example 7, not only can the shortcomings that cannot be recovered after the catalyst reaction be solved by simple filtering, but also the conversion rate of the product is improved simultaneously, and the product appearance obtained is clear and bright, stable performance, and the catalyst can be recycled and reused 4 times, which greatly reduces production costs and meets the sustainable development strategy.
[0068] Comparative Example 5
[0069] (1) Preparation of immobilized platinum complex catalyst: 4 mL of chloroplatinic acid-isopropanol solution was added with 15 mL of ethanol, where the molar fraction of platinum in the solution was 0.02 mol / L. After stirring evenly, 5.0 g of activated carbon was added. After impregnation for 36 h, the solution was dried at 90 °C to finally prepare an immobilized platinum complex catalyst.
[0070] (2) Preparation of polyether-modified siloxane: 9.27g of allyl polyether and 0.01g of immobilized platinum catalyst were added to a flask, stirred evenly without nitrogen, and heated to 75-80°C for catalyst activation for 30 minutes. Then 490.73g of siloxane with a molecular weight of 19306 and a hydrogen content of 0.2% was added to the above system, and the temperature was raised to 130°C for 8 hours. The molar ratio of siloxane to polyether added was 1.0:1.2, and the amount of catalyst was 20μg / g. Finally, the reaction conversion rate of silane in the reaction was determined by measuring the hydrogen content. After the reaction, the immobilized platinum catalyst was separated by filtration to obtain polyether-modified siloxane.
[0071] Comparative Example 6
[0072] (1) Preparation of immobilized platinum complex catalyst: Take 4 mL of chloroplatinic acid-isopropanol solution and add 15 mL of ethanol. The molar concentration of platinum element in the solution is 0.02 mol / L. After stirring evenly, add 5.0 g of aluminum oxide. After immersion for 36 hours, dry at 90°C to finally prepare an immobilized platinum complex catalyst.
[0073] (2) Preparation of polyether-modified siloxane: 163.62g of allyl polyether and 0.01g of immobilized platinum catalyst were added to a flask, stirred evenly without nitrogen, and heated to 75-80°C for catalyst activation for 30 minutes. Then 336.38g of siloxane with a molecular weight of 750 and a hydrogen content of 0.5% was added to the above system, and the temperature was raised to 120°C for 8 hours. The molar ratio of siloxane to polyether added was 1.0:1.2, and the amount of catalyst was 20μg / g. Finally, the reaction conversion rate of silane in the reaction was determined by measuring the hydrogen content. After the reaction, the immobilized platinum catalyst was separated by filtration to obtain polyether-modified siloxane.
[0074] The catalysts described in Comparative Examples 5-6 were only treated by impregnating the carrier with chloroplatinic acid solution, while the immobilized platinum catalysts in Examples 1-7 were prepared by adding polyethylene glycol as a complexing agent to the impregnation solution. The use of polyethylene glycol can better load the impregnation solution onto the carrier, thereby increasing the catalyst content on the carrier.
[0075] Test Example 1
[0076] Performance Determination of Polyether Modified Silicone
[0077] (1) Determination of hydrogen content: by sodium thiosulfate titration, take about 0.1g of the polyether-modified siloxane sample prepared in the above Examples 1-7 and Comparative Examples 1-6, place it in a 250mL iodine volume flask, take 20mL of carbon tetrachloride to dissolve it, then add 10mL of 0.2mol / L bromine-acetic acid solution and 0.5mL of water, shake well, seal with deionized water, place in a dark place to react for 30min, then add 25mL of 10% KI solution, rinse the bottle mouth with deionized water, drop 1% starch solution as an indicator, and titrate with 0.1mol / L sodium thiosulfate solution. When the solution changes from blue to colorless, it is the end point, and a blank test is performed at the same time. The calculation formula is as follows:
[0078] w=M(V0-V1)*0.5 / (G*1000)*100%
[0079] Where w is the active hydrogen mass fraction of the sample (%);
[0080] M is the molar concentration of sodium thiosulfate standard solution (mol / L)
[0081] V0 is the volume of sodium thiosulfate solution consumed by the blank sample (mL);
[0082] V1 is the volume of sodium thiosulfate solution consumed by the sample (mL);
[0083] G is the sample mass (g).
[0084] After calculating the mass fraction of active hydrogen, the conversion rate of Si-H can be calculated as follows:
[0085] Si-H conversion rate = (w0-w1) / w0*100%
[0086] Wherein, w0 is the mass fraction of active hydrogen before the reaction (%);
[0087] w1 is the mass fraction (%) of active hydrogen after the reaction.
[0088] The results of the conversion rate of polyether-modified siloxane and the color state of the product are shown in Table 1.
[0089] Table 1
[0090] Conversion rate (%) Product Color Status Example 1 88.3 transparent Example 2 86.5 transparent Example 3 88.4 transparent Example 4 89.7 transparent Example 5 90.2 transparent Example 6 93.5 transparent Example 7 96.8 transparent Comparative Example 1 87.0 Light yellow Comparative Example 2 86.0 Light yellow Comparative Example 3 89.4 Light yellow Comparative Example 4 87.9 Light yellow Comparative Example 5 90.3 transparent Comparative Example 6 87.2 transparent
[0091] As shown in Table 1, in the same synthesis process, the polyether-modified siloxane prepared by catalysis of immobilized platinum catalyst in Examples 1-7 is clear and transparent, and has a higher conversion rate. When the isopropanol solution of chloroplatinic acid is used as a catalyst to catalyze the hydrosilylation reaction in Comparative Examples 1-4, the product color is light yellow, and the conversion rate is relatively low. The catalyst used in Comparative Examples 5-6 is an immobilized platinum catalyst prepared without the addition of complexing agent polyethylene glycol, and the synthesis process is the same. By comparing Example 7 and Comparative Example 5, Example 5 and Comparative Example 6, it can be seen that: the catalyst obtained by adding the complexing agent polyethylene glycol impregnation, the catalyst dosage is less, and the catalytic polyether-modified siloxane conversion rate is higher, indicating that the immobilized platinum catalyst proposed by the present invention has a higher catalytic activity, and the catalyst increases the loading amount of platinum in the carrier due to the addition of polyethylene glycol.
[0092] (2) Determination of HLB value: Using the modified titration method of Greenwald: 0.2 g of the polyether-modified siloxane sample prepared in the above Examples 1-7 and Comparative Examples 1-6 was dissolved in 20 mL of dioxane / benzene (90% volume / 4% volume), and then titrated with distilled water until turbidity was clearly visible. The number of milliliters of water used is called the water value V. The HLB value is calculated using the water value V, and the calculation formula is as follows:
[0093] HLB=23.6lgV-10.6
[0094] The measurement results are shown in Table 2.
[0095] Table 2
[0096]
[0097] As shown in Table 2, the HLB values of the polyether-modified siloxanes in Examples 1-7 are close to those in Comparative Examples 1-6, indicating that the product obtained by the method for preparing polyether-modified siloxanes catalyzed by the immobilized platinum catalyst proposed in the present invention is more suitable for wetting and penetration.
[0098] (3) Determination of surface tension: Using a fully automatic interfacial tension meter, the polyether-modified siloxane sample was prepared into a solution with a mass fraction of 0.1% with deionized water. The solution temperature was controlled at 25° C. The corresponding aqueous solutions of the polyether-modified siloxane prepared in the above Examples 1-7 and Comparative Examples 1-6 were measured using a platinum ring method. The results were repeated three times and the average value was taken.
[0099] The measurement results are shown in Table 3.
[0100] Table 3
[0101]
[0102] As can be seen from Table 3, the surface tension of the products obtained by the synthesis process for preparing polyether-modified siloxanes of the present invention is generally low, and the surface tension values of the polyether-modified siloxanes prepared by the immobilized platinum catalyst proposed in the present invention, i.e., Examples 1-7, are even lower, and the surface tension of the product of Example 7 is only 19.5 mN / m.
[0103] (4) Determination of spreading area: Take 10 μL of the test solution with a pipette and drop it onto a plastic sheet marked with cells. After 120 seconds, count the number of cells to obtain the spreading area. Repeat three times and take the average value. The spreading area of the aqueous solution with a mass fraction of 0.1% of the polyether-modified siloxane prepared in Examples 1-7 and Comparative Examples 1-6 was measured by the above method.
[0104] The measurement results are shown in Table 4.
[0105] Table 4
[0106]
[0107] It can be seen from Table 4 that the aqueous solution of the polyether-modified siloxane prepared by the immobilized platinum catalyst in the embodiment of the present invention has a large spreading area, and it is particularly obvious that the polyether-modified siloxane prepared in Example 7 has excellent wetting properties.
[0108] Test Example 2
[0109] (1) Catalyst recycling performance test
[0110] The immobilized complex platinum catalyst proposed in the present invention is subjected to one hydrosilylation reaction, filtered, separated, dried and reused. The catalyst reusability is tested by repeating the hydrosilylation reaction in Example 7 and recording the siloxane conversion rate.
[0111] The measurement results are shown in Table 5.
[0112] Table 5
[0113] Repetitions 1 2 3 4 Conversion rate (%) 96.3 95.6 94.2 92.7
[0114] As can be seen from Table 5, the conversion rate of the polyether-modified siloxane prepared by using the immobilized platinum catalyst in the embodiment of the present invention after being reused 4 times is 92.7%, and the conversion rate can still be maintained at a high level, indicating that the catalyst proposed in the invention can be recycled.
[0115] In summary, the immobilized platinum catalyst prepared by the present invention can not only improve the catalytic activity of the catalyst, but also the obtained polyether-modified siloxane has excellent wetting properties and a clear and bright appearance, and the catalyst can be recycled, which greatly reduces the production cost and is conducive to sustainable development.
[0116] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.
Claims
1. A method for preparing a polyether-modified siloxane, characterized in that: The steps include: The polyether and the immobilized platinum catalyst are heated at 75-80° C. for 30-60 minutes, and then siloxane is added, and the temperature is raised to 120-140° C. for 5-8 hours, wherein the molecular weight of the siloxane is 250-20000 and the hydrogen content is 0.2%-1.0%; The preparation method of the immobilized platinum catalyst comprises: Dissolving polyethylene glycol and a platinum source in ethanol to obtain a mixed solution; Adding a carrier, impregnating, and drying to obtain the immobilized complex platinum catalyst; Wherein, the platinum source is chloroplatinic acid-isopropanol solution, and the molar concentration of platinum element in the mixed solution is 0.02 mol / L; The mass volume ratio of the polyethylene glycol to ethanol is 2.5 g:15 mL; The carrier is activated carbon, and the mass ratio of the carrier to polyethylene glycol is 5.0:2.5; The immersion time is 36 hours, and the drying temperature is 90°C; The molar ratio of the siloxane to the polyether is 1.0:1.2; based on the total mass of the siloxane and the polyether, the amount of the immobilized platinum catalyst is 10 μg / g.
2. A polyether-modified siloxane, characterized in that: It is prepared by the method of claim 1.
Citation Information
Patent Citations
Method for synthesizing polyether modified trisiloxane by using supported platinum catalyst
CN109957104A
Method for preparing beta-addition product by asymmetrical olefin hydrosilylation addition
CN1865263A